Influence of Internal Domestic Relations and Traditions on Efficiency of Moral Education of Rising Generation - Viktor Korolenko (Pedagogical Discourse, 2017)
In the article the necessity of moral education of rising generation is examined taking into account psychological and pedagogical scientific achievements, using in the process of education of national, domestic pedagogics and pedagogics of other people experience. Ability of the effective use of modern pedagogical knowledges is underlined. The results of the conducted research specify on the necessity of elucidation to the children about the important role of moral knowledges in lives of man, which will be instrumental in aspiring of growing up personality to moral perfection.Moral education – it one of forms of inheritance of morality in society. A moral is in understanding of modern society, is the synonym of ethics. Thus, under moral education it is possible to understand the process of the purposeful forming for the child of the moral settings, and also fixing of habits of conduct, proper to the norms and moral, accepted in society. Presently, when the standards of legal cruelty with people are widely presented in mass medias, entertaining transmissions and films, and also in computer games which children master from school age, moral education of children must spare the special attention. The research conducted by us confirms that in the process of increase of level of moral education and efficiency of forming of moral bases of rising generation a leading role is played by a seed and school, instrumental in their comprehensive development and preparation to modern life in society.The various aspects of this problems are reflected at the offered article which can be used to the students of higher educational establishments, by teachers, class leaders, workers of groups, sections, and others like that. The information expounded in the article will play up to all, who intends to choose the profession of teacher.